(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
The article reveals the theoretical, methodological and practical foundations of the organization of geography lessons on the basis of Bloom’s taxonomy. The article analyzes the issues of stage-by-stage development of cognitive activity of students, the formation of critical and creative thinking.